Gestión del Talento Humano para El Desarrollo Productivo y Su Impacto Ambiental de la Empresa Agrícola Grucowil S.A periodo 2013 - Coello Cevallos, Génesis Gabriela (2015)
This investigation was researched between the month of November 2013 and November 2014, in the town of Quevedo, Los Rios state with the purpose of analyzing the labour and talent of Grucowil corporation S.A which produce banana and African palm oil, and be able to make a better productivity not forgetting the impact that these class of plantations has in the environment. The main issued, that affect this company is the none existing policy for the procedure that apply to the better productivity and organization of the company. We have also investigated, on why the company is not applying the right methods and measures, focusing in questioning the employees of Grucowil S.A, we found that the main reason is the lack of resources and money. The company needs to have the right and qualified personnel for the duty’s to be carried out. Knowing that the right system of selecting and recruiting need to be put in place. As a consequence, multiples problems and hazards appeared, as we hire the wrong people for the job. Saying that the staff at Grucowil S.A has adapted to the limitations and difficulties and have carried on to the best of their compatibilities’ to get the job done. It is very important that the company update their policies with the world of labour and a safe working environment, they need to give the right training to all their personnel. Also, administration and human resources department need to be properly in place as this will be of great help and a advantaged for the company directors and employees.